2008
DOI: 10.1002/htj.20197
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer enhancement by pulsatile flows in grooved channels (the effects of groove length on the resonant mass transfer enhancement)

Abstract: The effect of groove length on the resonant mass transfer enhancement by pulsatile flow in grooved channel at intermediate Reynolds number was studied for five channels using experimental methods. The mass transport processes from the bottom of the groove to the channel were visualized by an electrolytic precipitation method, and overall and local mass transfer rates were measured by electrochemical methods with a high Schmidt number fluid. The qualitative and quantitative observations show that the range of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Jin [3] confirmed the existence of the optimum pulsation frequency for the maximum heat transfer enhancement. Nishimura [4,5] found that the optimal pulsation frequency depends on the opening size of rectangular groove and the Reynolds number. Kunitsugu [6] showed that for different groove sizes, the flow field structure within the groove showing large differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin [3] confirmed the existence of the optimum pulsation frequency for the maximum heat transfer enhancement. Nishimura [4,5] found that the optimal pulsation frequency depends on the opening size of rectangular groove and the Reynolds number. Kunitsugu [6] showed that for different groove sizes, the flow field structure within the groove showing large differences.…”
Section: Introductionmentioning
confidence: 99%
“…Nishimura [4,5] found that the optimal pulsation frequency depends on the opening size of rectangular groove and the Reynolds number. Kunitsugu [6] showed that for different groove sizes, the flow field structure within the groove showing large differences. He also indicated that there exists an optimal average Reynolds number corresponding to the maximum heat transfer enhancement factor depends on the groove size.…”
Section: Introductionmentioning
confidence: 99%